SILAC-based quantitative proteomics to investigate the eicosanoid associated inflammatory response in activated macrophages - Nicole Brace; Ian L. Megson; Adriano G. Rossi; Mary K. Doherty; Phillip D. Whitfield (BMC, 2022)
Abstract Background Macrophages play a central role in inflammation by phagocytosing invading pathogens, apoptotic cells and debris, as well as mediating repair of tissues damaged by trauma. In order to do this, these dynamic cells generate a variety of inflammatory mediators including eicosanoids such as prostaglandins, leukotrienes and hydroxyeicosatraenoic acids (HETEs) that are formed through the cyclooxygenase, lipoxygenase and cytochrome P450 pathways. The ability to examine the effects of eicosanoid production at the protein level is therefore critical to understanding the mechanisms associated with macrophage activation. Results This study presents a stable isotope labelling with amino acids in cell culture (SILAC) -based proteomics strategy to quantify the changes in macrophage protein abundance following inflammatory stimulation with Kdo2-lipid A and ATP, with a focus on eicosanoid metabolism and regulation. Detailed gene ontology analysis, at the protein level, revealed several key pathways with a decrease in expression in response to macrophage activation, which included a promotion of macrophage polarisation and dynamic changes to energy requirements, transcription and translation. These findings suggest that, whilst there is evidence for the induction of a pro-inflammatory response in the form of prostaglandin secretion, there is also metabolic reprogramming along with a change in cell polarisation towards a reduced pro-inflammatory phenotype. Conclusions Advanced quantitative proteomics in conjunction with functional pathway network analysis is a useful tool to investigate the molecular pathways involved in inflammation.